The Role of Infection and Immune Responsiveness in a Case of Treatment-Resistant Pediatric Bipolar Disorder - Greenberg, Rosalie (Frontiers in Psychiatry, 2017)
A case of psychotropic resistant pediatric bipolar disorder is presented. Both awareness and proper treatment of previously unrecognized infections and their the immune system effects were very important in stabilizing the patient.